Cameroon : Enhanced Heavily Indebted Poor Countries (HIPC) Initiative; Completion Point Document and Multilateral Debt Relief Initiative (MDRI). (IMF Staff Country Reports; Country Report, 2006)
This paper on Cameroon's Enhanced Heavily Indebted Poor Countries (HIPC) Initiative explains implementation of the poverty reduction strategy and macroeconomic performance. Executive Directors agreed that Cameroon's external public debt was above the HIPC Initiative sustainability threshold, and the country was eligible for assistance in the amount of USD 1.26 billion in 1999. Assuming prudent fiscal policies and robust non-oil real GDP growth, Cameroon's external public debt is expected to be sustainable over the long term.